Harmonizing research outcomes for polycystic ovary syndrome (HARP), a marathon not a sprint: current challenges and future research need. Issue 3 (17th December 2020) - Al Wattar, Bassel H; Bueno, Aurora; Martin, Miguel Garcia; Ibáñez, Naomi Cano; Harasani, Klejda; Garad, Rhonda; Franks, Steve; Balen, Adam; Bhide, Priya; Piltonen, Terhi; Romualdi, Daniela; Laven, Joop; et al.
ABSTRACT: Investing in clinical research and evidence-based medicine has helped to improve the care for women with polycystic ovary syndrome (PCOS). However, several important questions remain unanswered on the optimal prevention and management strategies for PCOS. Addressing this uncertainty is often hindered by suboptimal research conduct leading to inefficient evidence synthesis and research wastage. PCOS research is often practised by varied specialized teams in silo leading to disharmonious and fragmented efforts neglecting the lifelong impact of PCOS on women's wellbeing. Poor engagement among key stakeholders and lay consumers continues to limit the impact and benefits of research to society. Selective reporting on surrogate outcomes with a 'significant' P -value is a common malpractice in PCOS outputs. Effective adoption of the harmonizing research outcomes for PCOS (HARP) core outcome set is needed to minimize heterogeneity in reporting and promote research excellence. Small single-centre studies offer limited value to assess the varied PCOS phenotypes. Efficient large scale data-sharing is needed to address complex research questions and glean the benefits of big data research. We propose a roadmap to address these challenges and remedy future research need by promoting patient and public involvement in PCOS research to guide research efforts and address real patients' needs; engaging all key stakeholder groups to promote a multi-disciplinary lifelong approach to new research; continuously refining research needs and priorities to revise the knowledge gap and allocate resources judiciously; standardizing outcomes definitions and measurement tools to harmonize reporting and promote excellence in research; and by investing in large data-sharing infrastructure to facilitate big data research and govern ethical data sharing.